Effects of Surface Finish Material on Millimeter-Wave Antenna Performance - Usta, Ersin; Tokan, Nurhan Turker (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
Recently, the popularity of millimeter-wave circuits has increased. One of the main reasons for this increase is offering a wide frequency band and high-speed data transfer. Due to the manufacturing requirements, these circuits are covered with surface finishes. Although surface finish protects the exposed copper circuitry, these additive layers on copper foil affect the electrical properties of the conductor. Unlike previous papers in the literature, this paper deals with the effects of surface finishing materials on millimeter-wave antennas instead of transmission lines. With this aim, a differential dual exponentially tapered slot antenna (DETSA) that has almost constant gain, beamwidth, and low reflection coefficient over the entire V-band is designed. A balun is designed for one-port measurement of the differential antenna. Then, two widely used surface finish solutions, namely, electroless nickel immersion gold (ENIG) and immersion silver (IAg), are applied to the copper profile of the differential integrated antenna combined with balun. The structures are simulated with a widely used full-wave analysis tool. The antenna without surface finish, with ENIG, and IAg surface finishes are fabricated and measured. A peak gain of 8.7-9 dBi is measured in the 57-64-GHz ISM band for the antenna without surface finish. Only 0.2-dB decrease in maximum gain is observed with 0.4-mu m silver. With ENIG surface finish, the gain decrease is observed as 1 dB. ENIG has higher loss due to flow of current in nickel material having lower conductivity compared to copper. The measurement results are consistent with the numerical results.
Keywords: 60 GHz; differential antenna; dual exponentially tapered slot antenna (DETSA); millimeter wave; printed circuit board (PCB); surface finish material; METHODOLOGY; Engineering; Materials Science